Principles and Constants of the Golden Proportion as a Criterion in Donosological Diagnostics of the Functional States of The Body and in the Assessment of the Probability of their Changes - Karabayev M.; M. Gasanova N.; T. Botirov M.; Kosimova G.S. (International Physiology Journal, 2022)
A theoretical paper proposes applications of golden proportion principles to physiological diagnostics. It outlines proposed metrics and discusses validation needs and limitations.
Keywords: functional state